A RHETORO-PRAGMATICS ANALYSIS OF CHRISTIAN PRAYERS: FORM, STRUCTURE AND FUNCTIONS - ADEYANJU, Adegboye (EBSU Journal of Social Sciences and Humanities, 2024)
This study investigates the rhetorical-pragmatics of prayers usually located within the exordium/introduction of African or African-America Charismatic Christian sermons. For the study, a corpus of prayers from the Holy Ghost Service, the pre-eminent ritual event of the Redeemed Christian Church of God, RCCG, Lagos-Nigeria was gathered through three main sampling methods: a) purposive (non-probability), b) stratified, and c) random sampling were employed. Through purposive sampling commencing from 2006-2012 seventy-two (72) HGS sermonswere first selected for the 6-year period. To select prospective HGS sermons from the population of HGS sermons performed over the 6-year period, using an interval of every three years, all the 2006, 2009 and 2012 HGS sermons were tabulated. Two HGS lists, one each for March and December were drawn for each selected year. Every nth HGS sermon was then selected from each list. Going by these lists, (3) March and (3) December HGS were selected for the period 2006 to 2012 to generate a sample of 6 HGS. Insofar as the present study represents a descriptive and exploratory study, this (6) HGS sermons sample is deemed appropriate to providing data that could be reasonably handled in this study. Study findings indicates prayer is an illocutionary act, one that through the force of utterance contribute to unfolding events perceived as action willed or permitted by divine beings and assented to or challenged by human beings, therefore prayer is a form of religious expression and can be considered as discourse that deserves rhetorical analysis. Also, that prayer as speech act has a defined and patterned structure codified through usage from ancient times: (a) address or invocation; (b) arguments in support of the request; and (c) the request. This is the classical structure of prayer which is found in many religious texts and practices. So, ‘the three-part prayer’ would equally represent the implementation of a logically constructed rhetorical structure which is executed by religious adherents in support of a request to an Unseen deity. Finally, that the purpose of prayer appears to be the development of argumentation and persuasion in support of the request by the one who prays or is praying